Research on Association of the Diameter of the Internal Carotid Artery Siphon and Nonarteritic Anterior Ischaemic Optic Neuropathy - Zhiyong Fu; Hongyang Li; Wei Wang; Yanling Wang (Journal of Ophthalmology)
Objective. To investigate the association of the diameter of the internal carotid artery siphon (ICAS) and nonarteritic anterior ischaemic optic neuropathy (NAION). Methods. Thirty patients clinically diagnosed with NAION (unilateral affected) who presented to Beijing Friendship Hospital from January 2017 to October 2018 were selected. The eyes suffered from NAION were enrolled as the observation group, and the fellow healthy eyes were enrolled as the control group. The following indexes were measured: diameter of the ICAS and the ophthalmic artery (OA), intima-media thickness (IMT) of the internal carotid artery (ICA), degree of stenosis of the ICA and plaque formation, and hemodynamic parameters of the ICA and the short posterior ciliary arteries (SPCAs). All the values were compared between the two groups. Results. The diameter of the ICAS in the observation group (0.30 ± 0.07 cm) significantly narrowed compared with that of the control group (0.32 ± 0.06 cm) (P<0.05), but the diameter of the OA of the two groups had no significant difference. The detection rate of carotid atherosclerosis plaque, the average blood flow velocity (Vm), and the resistance index (RI) of the ICA in the observation group (46.67%, 26.81 ± 1.78 cm/s, and 0.72 ± 0.06) had significant differences compared with those of the control group (16.67%, 28.19 ± 2.75 cm/s, and 0.70 ± 0.05) (P<0.05), but the gradings of ICA stenosis and IMT between the two groups had no significant differences. The peak systolic velocity (PSV) and the end diastolic velocity (EDV) of the SPCAs in the observation group (10.72 ± 2.88 cm/s and 3.43 ± 1.01 cm/s) were significantly lower than those of the control group (13.62 ± 3.93 cm/s and 4.59 ± 1.71 cm/s) (P<0.05), but the RI of the SPCAs of the two groups had no significant differences. Conclusion. The diameter of the ICAS has a close relationship with NAION.